The tension between global public procurement law and nationalist/populist tendencies: proposals for reform - Miranzo-Díaz, Javier (Revista de Investigações Constitucionais, 2020)
GPA had a main objective from its very beginning: confronting discrimination between bidders on national or geographical grounds and opening the system up to greater competence between private actors. The World has experienced a gradual liberalization of public national markets that was almost perceived as a natural process. But this other time thought never-ending process is experiencing serious difficulties. The global political panorama seems to be moving again towards the once forgotten nationalist ideologies; a fact that has brought back again the old host of economic protectionism to the front line of international public markets regulation. The present paper analyses the existing situation from a critical approach. Firstly, it carries out a study of the mechanisms and motives that lie behind populisms and its relationship with international law legitimacy and traditional procurement bias. Secondly, it signals the central role of GPA as the main international instrument to face neo-protectionism, and focuses on the subtle nature of most procurement barriers and how current review mechanism fail to both efficiently tackle potential infringements and to guarantee states’ autonomy. Finally, a proposal for reform is made as to the functioning of the GPA review mechanisms through the creation of a mixed review system.